Modelling and Performance Analysis of an Electric Vehicle Powered by a PEM Fuel Cell on New European Driving Cycle (NEDC) - Işıklı, Fırat; Sürmen, Ali; Gelen, Ayetül (Springer Science and Business Media Deutschland GmbH, 2021)
Modelling of a complete polymer electrolyte membrane fuel cell (PEMFC) power systems and performance of the models when subjected to common driving cycle are important research issues. In this study a complete PEMFC system, including air and hydrogen supply equipment, fuel cell stack, electrical system and a 75 kW car, is modelled. An efficiency map of a brand new electric motor is directly imported into the model for it. MATLAB & Simulink tools, based on this mathematical model of PEMFC, are used to establish a dynamic model for a vehicle which is electrically supplied by the fuel cell according to cruise characteristics of New European Driving Cycle (NEDC). Model results show significant instabilities during transient operation regarding the late response of the air supply system. Obtained stack characteristics are similar to those obtained in similar studies conducted previously. Performance results of the car based on energy consumption shows perfect agreement with the results of another model developed for an electric vehicle of the same weight and run also on NEDC.
Keywords: Driving cycle; Fuel cell; Fuel cell modelling; Fuel cell vehicle; PEM fuel cell